A poesia polimorfa de Francisco Alvim - Guimarães, Leandro Bernardo (2017)
Poetry, centered on the expression of the first person of discourse, crystallized in the collective imaginary as the enunciative space of "lyrical self." Associated, at first, with the revelation of the emotional layers of the empirical poet, this concept become fragile, above all, from the literary Modernity, when the idealistic values are questioned in favor of a materialist view. This paradigmatic change will imply in the understanding of the human being as a subject fragmented by the incongruities of the historical process, which will result, in the lyric, in the configuration of subjectivities increasingly dissociated from the vision of a subject centered and intact, as thought from the seventeenth century . In the panorama of contemporary Brazilian poetry, in relation to the work around the construction of the lyrical subject, the work of Francisco Alvim stands out. From the publication of his first book, the blind men's Sun (1968), that constituent line of the lyrical gender has been a subject that the restless. Starting from a subjective configuration centered on the experiential experience of a "self", characteristic of his initial phase, it gains strength in his diction, mainly from his second work, Pastime (1964), poems in which there is the predominance of decentralization and the depersonalization of subjective speech. This procedure gives rise to voices and personas who, often in dialogue, make the poem a space of dramatization of subjectivity. This technique, which allows the enunciation of the "lyrical self" to the voice of the other, it makes possible the poet to denounce the violence forms that are naturalized by the society and for the State. Theoretical studies around the lyrical subject, such as those of Michel Collot (2013) and those of Michael Hamburger (2007); Studies on recent Brazilian poetry, such as those of Benedito Nunes (2009) and those of Iumna Maria Simon (1999); Critical studies on Francisco Álvim's lyric, such as those of Carlos Antonio de Brito (1988) and those of Roberto Schwarz (2002) support our reflections.